Performance of selected Islamic banks in Malaysia : A comparative study - Nik Nor Amalina, Nik Mohd Sukrri (2014)
The objective of this paper is to examine the performance of selected Islamic banks in Malaysia which are Bank Islam Malaysia Berhad (BIMB), RHB Islamic Bank Berhad (RHB Islamic) and Bank Muamalat Malaysia Berhad (BMMB) in the period between year 2005 until 2012. A comparative study is undertaken based performance indicators such as return on assets (ROA), return on equity (ROE), profit generated by each year and Islamic modes of finance such as mudarabah, musharakah, murabahah, ijarah and istisna. The methodology that use in this study are descriptive analysis, one way ANOVA and Kruskal Wallis for parametric test as well as T-Tests and Wilcoxon for non-parametric test using data from annual reports of the banks. All the analysis are used in determining their significance. The study found that there are no differences in performance and profit of Bank Islam, RHB Islamic and Bank Muamalat. However, the study finds that there are significant differences in Islamic modes of finance except for Istisna contract.